Wax and wicks - Ibrahim, Faridah Hanum; Baharuddin, Mohd Nasir; Mad Halid, Norhidayah (Universiti Putra Malaysia Press, 2017)
Ever wondered how candles are made? It is always with wax and wicks. Thus, a candle has a wick that is embedded in a wax to provide light and sometimes fragrance.